Argilominerais da Formação Codó (Aptiano Superior) – Bacia de Grajaú: implicações ambientais e climáticas. - GONÇALVES, Daniele Freitas (Universidade Federal do Pará, 2019)
The Codó Formation is exposed in the adjacency of the town of Codó (MA) and consists of a dominantly closed and hypersaline lacustrine setting. It is characterized by sucessions that are arranged into shoaling upward cycles averaging 1 m thick. The cycles are constituted upward by central lake deposits (i.e., evaporite and bituminous black shale), transitional lake deposits (i.e., laminated argillite, lime-mudstone, peloidal packstone and meso-crystalline carbonate) and marginal lake deposits (i.e., massive pelite, gipsarenite and calcarenite with fenestrae and features of palaeokarst, pisoidal packstone to grainstone, rhythmite and nodular chert). This work applied X-ray diffraction and microscopic (including scanning electron microscopy) analyses to investigate argillaceous rocks of the Codó Formation. The goals included the characterization of the clay mineral assemblage, definition of its nature and evaluation of its application as a paleoclimatic and paleoenvironmental indicator. The facies studied in this work included: black shale, laminated argillite, lime-mudstone, massive pelite and rhytmite of carbonate and shale. These facies showed a clay mineral assemblage composed of smectite and, subordinately, illite kaolinite and interstratified illite-smectite. The smectite is, in general, detrital in nature, being characterized by crenulated flakes with parallel or chaotic arrangements. The smectite, when pure, exhibit high cristallinity and/or interstratification and has been classified as dioctaedric montmorillonite. Authigenic smectite can be locally found and is arranged in crystals averaging 2μm that show a honeycomb morphology, usually drapping ostracode shells in rhythmites. Kaolinite occurs as pseudohexagonal and equidimensional crystals averaging 1μm in diameter that replaces the smectite, and as booklets (averaging 8μm) that fill vugs. Its occurrence is substantially increased in marginal lake deposits, more specifically in the massive pelite facies. Illite occurs as hair-like crystals in transitional lake deposits as replacement of smectite. It is possible that part of the illite is detrital; in this case, it is characterized by a morphology in flakes that can hardly be differentiated from detrital smectites. The distribution of clay minerals throughout the studied profiles shows an upward decrease in both the amount and the crystallinity and/or interstratification of smectite. This tendency was also observed in some individual shoaling-upward cycles. Thus, central and transitional lacustrine deposits, located at the base of the sucessions, exhibit relatively increased amounts of smectite relative to kaolinite and illite, while the transitional and marginal deposits at the top show an inverse behavior. The dominance of detrital smectite and the large occurrence of evaporites in the study area confirm a warm and semi-arid climate during the late Aptian in the Grajaú Basin. The variability of clay minerals along the profiles correlates well with shoaling upward cycles, helping to better define them. The genesis of the authigenic clay minerals (i.e., kaolinite and illite) has been credited to pedogenic processes. The coexistence of kaolinite and illite is related to alternations between wet and dry periods.